2020
DOI: 10.3390/biology9090265
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil Conversion Pathway Mutations in Gastric Cancer

Abstract: To date, 5-Fluorouracil (5FU) is a major component of several chemotherapy regimens, thus its study is of fundamental importance to better understand all the causes that may lead to chemoresistance and treatment failure. Given the evident differences between prognosis in Asian and Caucasian populations, triggered by clear genetic discordances and given the extreme genetic heterogeneity of gastric cancer (GC), the evaluation of the most frequent mutations in every single member of the 5FU conversion and activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…It is to date well established the involvement of the thymidine phosphorylase-thymidylate synthase axis in 5-FU metabolism and activation. As already reported [18] TYMP in particular plays a major role also in angiogenesis interacting with several pro-angiogenic factors. Indeed, evaluating such markers by qPCR, we evidenced a significant upregulation of both TYMP and TYMS in 5FUr cells, as shown in Figure 5a.…”
Section: Tymp As the Key Between Vascularization And 5-fu Metabolismsupporting
confidence: 61%
See 3 more Smart Citations
“…It is to date well established the involvement of the thymidine phosphorylase-thymidylate synthase axis in 5-FU metabolism and activation. As already reported [18] TYMP in particular plays a major role also in angiogenesis interacting with several pro-angiogenic factors. Indeed, evaluating such markers by qPCR, we evidenced a significant upregulation of both TYMP and TYMS in 5FUr cells, as shown in Figure 5a.…”
Section: Tymp As the Key Between Vascularization And 5-fu Metabolismsupporting
confidence: 61%
“…This phenomenon is routinely observed in clinical practice, when repeated chemotherapy treatments cause an initial reduction of the tumor mass, until a resistant cell subset arises from the heterogeneous pool of mutated cells and starts to grow back. These chemo- and radio-resistant cells often gain invasive and migratory capacities leading to cancer cell spreading and formation of metastases in distant tissues [ 18 ]. The tumor microenvironment might also contribute to chemoresistance, generating an intricate net of endothelial vessels to allow the tumor mass to reach a continuous source of nutrients and oxygen but preventing the delivery of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, ASS1, a signaling pathway involved in the regulation of metabolic genes, promotes GC invasion and progression mainly through the regulation of autophagy[ 29 ]. TYMS5 is involved in the fluorouracil conversion pathway,which is associated with chemoresistance and treatment failure by 5-FU in GC[ 48 ]. Kong et al [ 49 ] reported that MIF is associated with the p53 pathway in GC[ 49 ].…”
Section: Metabolic Genes Involved In Regulatory Pathways Of Gcmentioning
confidence: 99%